2009
DOI: 10.1007/s10811-009-9494-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a glucose-6-phosphate isomerase involved in adaptation to salt stress of Dunaliella salina

Abstract: The unicellular green alga Dunaliella salina is a recognized model for studying plant adaptation to high salinity. To isolate some salt-induced proteins at proteomics levels and to identify their expressions at gene levels, algal cells at logarithmic phase cultured in 1.5 and 3.5 M NaCl media were harvested for protein extraction. Solubilized proteins were applied to two-dimensional gel electrophoresis (2-DE) and analyzed by ImageMaster 2D Platinum software. Twenty-one protein spots whose intensities were elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The induction of trehalosephosphate synthase/phosphatase points towards a decreased activity of glycolysis (GL), as this enzyme is considered an important pacemaker of cytoplasmic carbohydrate breakdown [25]. Furthermore, the up-regulation of several other regulatory enzymes involved in GL ([26], [27]) and the PPP ([28], [29]) under OA suggests altered fluxes of carbon through the metabolism: GL and PPP are the main pathways competing for cytoplasmic glucose-6-phosphate. GL and subsequent oxidative reactions of the mitochondrial tricarboxylic acid cycle generate NADH mostly destined for respiration.…”
Section: Resultsmentioning
confidence: 99%
“…The induction of trehalosephosphate synthase/phosphatase points towards a decreased activity of glycolysis (GL), as this enzyme is considered an important pacemaker of cytoplasmic carbohydrate breakdown [25]. Furthermore, the up-regulation of several other regulatory enzymes involved in GL ([26], [27]) and the PPP ([28], [29]) under OA suggests altered fluxes of carbon through the metabolism: GL and PPP are the main pathways competing for cytoplasmic glucose-6-phosphate. GL and subsequent oxidative reactions of the mitochondrial tricarboxylic acid cycle generate NADH mostly destined for respiration.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we performed qRT-PCR analyses normalized using the optimal RGs to detect the expression patterns of six target genes (GPI, HIF1A, HSP20, HSP70, HSP90, and USP) associated with adaptation to extreme environments. Previous studies have shown that variation in the expression of GPI can improve the ability of organisms to adapt to extreme environments, such as high salinity and hypoxia (Cui et al, 2010;Naughton, 2003). Low oxygen supply is a major challenge for species living at high altitudes ; thus, hypoxia may be a key ecological factor driving changes in GPI expression in the grassland caterpillar.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is essential for all living organism to utilize the energy from carbohydrates. Regarding plants, it was identified to be a salt-induced protein in the green algae Dunaliella salina [ 59 ]. Under salt stress, glucose-6-phosphate isomerase is increased and involved in adaption to high salinity [ 59 ].…”
Section: Resultsmentioning
confidence: 99%